A copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide and preparation method thereof
By using soluble organic compounds as carbon sources, carbon-modified copper-based catalysts were prepared by co-precipitation-in-situ carbonization-reduction method, the problems of insufficient stability and selectivity of existing copper-based catalysts were solved, and efficient carbon dioxide hydrogenation synthesis was achieved Methanol.
Patent Information
- Application Number
- CN202310893671.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The existing copper-based catalysts used for hydrogenation of carbon dioxide to produce methanol have problems such as low carbon dioxide conversion and methanol selectivity and poor catalyst stability.
Carbon-modified copper-based catalysts were prepared by co-precipitation-in-situ carbonization-reduction method to ensure uniform mixing and tight bonding of carbon and copper-based catalysts.
The selectivity of methanol and the heat resistance stability of the catalyst were significantly improved. The selectivity of methanol was as high as 95%, and the CO2 conversion and methanol selectivity remained almost unchanged after heat resistance of 350°C.
Smart Images

Figure CN117085689B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, in particular to a copper-based catalyst for preparing methanol by hydrogenating carbon dioxide and a preparation method thereof. Background Art
[0002] With the development and improvement of human industrial civilization, the use of fossil fuels has continued to increase, and carbon dioxide emissions have increased year by year. High carbon dioxide emissions will accelerate global warming, ocean acidification, land desertification and other problems. Therefore, carbon dioxide emission reduction and resource utilization have become a research hotspot in today's society.
[0003] CO 2 It is a resource-based utilization of CO2. 2 Among various hydrogenation products, methanol is the first choice because methanol is a clean energy that can largely improve a country's energy depletion crisis. It is also a good hydrogen energy carrier. Using methanol fuel instead of fossil fuel as an energy storage medium can improve the energy crisis in the oil and gas era and alleviate the pressure of global warming. This has become a CO 2 Based on the above advantages, the synthesis of methanol by hydrogenation of carbon dioxide has important environmental protection potential and economic value.
[0004] Currently, copper-based catalysts used for hydrogenation of carbon dioxide to methanol have problems such as low carbon dioxide conversion rate and methanol selectivity, and poor catalyst stability. Researchers have achieved some results by adding metal additives such as Ga[Appl.Catal.BEnviron, 2013, 142-143, 241-248]., In[Appl.Catal.A, 2020, 605, 117805], etc., and the methanol selectivity has been improved, but the stability has not been significantly improved. Some researchers have also added carbon materials to improve catalyst stability. Because carbon materials are hydrophobic, they can effectively improve the effect of water produced during the reaction on the active components and prevent the growth and inactivation of ZnO. However, the copper-based catalysts modified with carbon materials reported so far are all directly added to copper-based catalysts in the form of carbon nanotubes [Catal.Today, 2018, 307, 212–223] and graphene [Chem.Eng.J, 2018, 334, 1781-1791]. Since carbon is insoluble, the prepared catalyst has problems such as uneven mixing of carbon and other components in the copper-based catalyst and difficulty in repeating.
[0005] In view of the above problems, the present invention adopts soluble organic compounds as carbon sources and prepares a uniformly mixed carbon-modified copper-based catalyst by in-situ carbonization, which can improve methanol selectivity and thermal stability of the catalyst. Summary of the invention
[0006] Based on the problems existing in the copper-based catalysts currently used for the hydrogenation of carbon dioxide to methanol, the object of the present invention is to provide a copper-based catalyst for the hydrogenation of carbon dioxide to methanol and a preparation method thereof. The present invention uses copper salt, zinc salt, zirconium salt or aluminum salt as raw material, carbonate as precipitant, and adds a carbon source as an auxiliary agent. The prepared copper-based catalyst for the hydrogenation of carbon dioxide to methanol has high CO 2 Conversion rate, methanol selectivity, high stability and other characteristics.
[0007] The invention discloses a copper-based catalyst for preparing methanol by hydrogenating carbon dioxide. The components of the catalyst include Cu, ZnO, ZrO 2 or Al 2 O 3 and additive C, Cu, ZnO, ZrO in the catalyst 2 or Al 2 O 3 The additive C is evenly dispersed on the catalyst surface and is tightly combined with the active component copper species to promote the dispersion of the copper species. At the same time, it plays a certain confining role on the copper species and enhances the hydrophobicity of the catalyst surface, so that the valence state of the copper species remains stable.
[0008] Furthermore, the present invention also defines that the components in the catalyst are expressed in molar percentage as follows: Cu is 20-70%, Zn is 10-60%, Zr or Al is 1-20%, and C is 1-30%.
[0009] Furthermore, the present invention also defines a method for preparing a copper-based catalyst for preparing methanol by hydrogenating carbon dioxide, which uses a copper source, a zinc source, a zirconium source or an aluminum source as a raw material, sodium carbonate as a precipitant, and a soluble organic compound as a carbon source, and adopts coprecipitation-in-situ carbonization-reduction to obtain a carbon-modified copper-based catalyst, which specifically includes the following steps:
[0010] 1) According to the feed ratio, a copper source, a zinc source, a zirconium source or an aluminum source is dissolved in water to prepare a metal salt solution; sodium carbonate is dissolved in water to prepare a sodium carbonate solution, and a carbon source is added into the water and ultrasonically stirred to obtain a solution containing a carbon source;
[0011] 2) co-precipitating the metal salt solution and the sodium carbonate solution into a solution containing a carbon source under stirring, aging under stirring, and filtering and washing the precipitate to obtain a catalyst precursor;
[0012] 3) After drying the catalyst precursor obtained in step 2), calcining it in an inert atmosphere for in-situ carbonization, and then 2 / N2 The catalyst is subjected to reduction treatment to obtain a carbon-modified copper-based catalyst.
[0013] Furthermore, the present invention also limits the carbon source to one or more of β-cyclodextrin, polyethylene glycol (PEG), ethylene glycol (EG), glucose or soluble starch.
[0014] Furthermore, the present invention also defines that the copper source is copper nitrate or copper acetate; the zinc source is zinc nitrate or zinc acetate; the zirconium source is zirconium nitrate or zirconyl nitrate; and the aluminum source is aluminum nitrate or pseudo-boehmite.
[0015] Furthermore, the present invention also defines the molar ratio of the total molar amount of the copper source, zinc source, zirconium source or aluminum source to carbon as 1:0.01-0.3.
[0016] Furthermore, the present invention also defines the specific operation of step 2) as follows: at 10-80°C, the metal salt solution and the sodium carbonate solution are titrated in parallel into the solution containing the carbon source in step 1) and stirred for co-precipitation, maintaining the pH value at 7-10, and after precipitation, the solution is stirred and aged at 40-100°C for 0.5-24h, and the precipitate is washed with deionized water until no sodium ions are detected to obtain a catalyst precursor.
[0017] Furthermore, the present invention also defines the catalyst precursor drying conditions in step 3) as: drying at 60-160° C. for 10-15 h; and the calcination conditions as: calcining at 300-500° C. for 3-6 h in a nitrogen or argon atmosphere.
[0018] The copper-based catalyst for preparing methanol by hydrogenating carbon dioxide of the present invention is used for preparing methanol by hydrogenating carbon dioxide, and the carbon dioxide raw gas composition is 10-30 vol.% CO 2 、30%~90vol.%H 2 and N 2 Mixed gas is used as balance gas, in which CO 2 With H 2 The volume ratio is about 1:3, using a fixed bed reactor, with a pressure of 2-10 MPa, a temperature of 180-280°C, and a space velocity of 6000-30000 mL g cat -1 h -1 CO 2 Hydrogenation to methanol reaction.
[0019] By adopting the above technology, compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] 1) The present invention uses copper salt, zinc salt, zirconium salt or aluminum salt as raw materials, carbonate as precipitant, and soluble carbon source as auxiliary agent, adopts coprecipitation-in-situ carbonization method, in-situ generates carbon on the copper-based catalyst, and synthesizes carbon-modified copper-based catalyst. The catalyst is modified by in-situ carbonization to generate carbon, so that the auxiliary agent and copper species are fully mixed, and the interaction is stronger;
[0021] 2) The carbon component in the catalyst of the present invention has a certain confinement effect on the copper species and enhances the hydrophobicity of the catalyst, thereby improving the selectivity of the catalyst in the synthesis of methanol by hydrogenation of carbon dioxide and the heat stability of the catalyst. The methanol selectivity is as high as 95%, and the heat stability of CO after 350°C is 0. 2 The conversion and methanol selectivity remained almost unchanged;
[0022] 3) The catalyst of the present invention is used in the synthesis of methanol by hydrogenation of carbon dioxide. The reaction byproduct is only CO, and the liquid product contains only methanol and water, which are easy to separate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the EDS-mapping image of the copper-based catalyst β-CZZ prepared in Example 1;
[0024] Figure 2 The contact angle measurement diagram of the copper-based catalyst prepared in Example 1 and Comparative Example 1;
[0025] Figure 3 This is a schematic diagram of the structure of the copper-based catalyst prepared in Example 1. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments, but the scope of protection of the present invention is not limited to the described scope.
[0027] Example 1
[0028] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1alkali solution 2; accurately weigh 0.14g of β-cyclodextrin and add it to 100mL of deionized water to prepare a carbon source solution 3; co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source solution 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ), a carbon-modified copper-based catalyst having a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05 was obtained, named β-CZZ. The schematic diagram of the copper-based catalyst structure is shown in Figure 3 shown.
[0029] Example 2
[0030] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2; accurately weigh 0.027g of β-cyclodextrin and add it to 100mL of deionized water to prepare a carbon source solution 3; co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source solution 3 under stirring at 70°C, the precipitation process needs to be fully stirred, and the pH is maintained at 7. After precipitation, it is aged at 70°C for 2h, and the precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12h, N 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.01, which was named β-CZZ-1.
[0031] Example 3
[0032] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2; accurately weigh 0.27g of β-cyclodextrin and add it to 100mL of deionized water to prepare a carbon source solution 3; co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source solution 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.1, which was named β-CZZ-10.
[0033] Example 4
[0034] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1alkali solution 2; accurately weigh 0.81 g of β-cyclodextrin and add it to 100 mL of deionized water to prepare a carbon source solution 3; co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source solution 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2 hours. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12 hours. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ), a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.3 was obtained, and was named β-CZZ-30.
[0035] Example 5
[0036] According to the molar ratio of Cu, Zn and Al of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g、Al(NO 3 ) 3 9H 2 3.75 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2; accurately weigh 0.14g of β-cyclodextrin and add it to 100mL of deionized water to prepare a carbon source solution 3. Co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source solution 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and aluminum source to carbon of 1:0.05, which was named β-CZA.
[0037] Example 6
[0038] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Solution 1. Accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2. Accurately weigh 0.11 g of PEG-40000 and add it to 100 mL of deionized water to prepare a carbon source solution 3. Co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source solution 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2 h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12 h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05, which was named PEG-CZZ.
[0039] Example 7
[0040] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Solution 1. Accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1alkali solution 2. Accurately weigh 0.16g of ethylene glycol and add it to 100mL of deionized water to prepare carbon source solution 3. Co-precipitate metal salt solution 1 and alkali solution 2 into carbon source solution 3 under stirring at 70℃. The precipitation process needs to be fully stirred, pH=7, and aged at 70℃ for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110℃ for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05, which was named EG-CZZ.
[0041] Example 8
[0042] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Solution 1. Accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2. Accurately weigh 0.14g of soluble starch and add it to 100mL of deionized water to prepare carbon source solution 3. Co-precipitate metal salt solution 1 and alkali solution 2 into carbon source solution 3 under stirring at 70℃. The precipitation process needs to be fully stirred, pH=7, and aged at 70℃ for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110℃ for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05, which was named S-CZZ.
[0043] Example 9
[0044] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 )2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Solution 1. Accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2. Accurately weigh 0.15g of glucose and add it to 100mL of deionized water to prepare carbon source solution 3. Co-precipitate metal salt solution 1 and alkali solution 2 into carbon source solution 3 under stirring at 70℃. The precipitation process needs to be fully stirred, pH=7, and aged at 70℃ for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110℃ for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05, which was named GLC-CZZ.
[0045] Comparative Example 1
[0046] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1Alkali solution 2; metal salt solution 1 and alkali solution 2 are co-precipitated into 100 mL of deionized water under stirring at 70°C. The precipitation process needs to be fully stirred, pH = 7, and aged at 70°C for 2 h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12 h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ), and the obtained catalyst was named CZZ.
[0047] Comparative Example 2
[0048] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 ) 2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Solution 1. Accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2. Accurately weigh 0.06g of CNTs and add it to 100mL of deionized water to prepare a carbon-containing suspension 3. Co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon source suspension 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ) to obtain a carbon-modified catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05, which was named CNTs-CZZ.
[0049] Comparative Example 3
[0050] According to the molar ratio of Cu, Zn and Zr of 6:3:1, Cu(NO 3 ) 2 ·3H 2 O 14.50g, Zn(NO 3 )2 6H 2 O8.93g, Zr(NO 3 ) 4 ·5H 2 4.29 g of O was dissolved in 100 mL of deionized water to prepare a total metal ion concentration of 1 mol L -1 Metal salt solution 1; accurately weigh Na 2 CO 3 15.90 g was dissolved in 150 mL of deionized water to prepare 1 mol L -1 alkali solution 2; accurately weigh 0.06g of GO and add it to 100mL of deionized water to prepare a carbon-containing suspension 3; co-precipitate the metal salt solution 1 and the alkali solution 2 into the carbon-containing suspension 3 under stirring at 70°C. The precipitation process needs to be fully stirred, and the pH is maintained at 7. The precipitate is aged at 70°C for 2h. The precipitate is washed with deionized water until no sodium ions are detected, and dried at 110°C for 12h. 2 Calcinate at 400℃ for 4h in atmosphere, then introduce 20% H 2 / N 2 The catalyst was reduced (30 mL min -1 ), and the obtained carbon-modified copper-based catalyst with a total molar ratio of copper source, zinc source, and zirconium source to carbon of 1:0.05 was named GO-CZZ.
[0051] Comparative Example 4
[0052] Industrial copper-zinc-aluminum methanol synthesis catalyst (industrial catalyst-1).
[0053] In order to evaluate the catalytic performance of the prepared catalyst, the catalyst was subjected to CO 2 Hydrogenation methanol synthesis performance test. A fixed bed reactor was used, and various catalysts were added. The flow rate was 50 mL min -1 CO 2 / H 2 / N 2 (23:69:8) mixed gas, and CO 2 The results of the hydrogenation reaction to synthesize methanol are shown in Table 1.
[0054] Table 1 Evaluation results of reaction performance of each example
[0055]
[0056] Reaction conditions: T = 220 °C, P = 3.0 MPa, H 2 / CO 2 =3, WHSV = 6000mLg cat -1 h -1
[0057] From the results listed in Table 1, it can be found that the catalyst of the present invention uses a soluble carbon source as an auxiliary agent, and the catalyst is modified by in-situ carbonization to generate carbon, thereby improving the activity and methanol selectivity of the copper-based catalyst and significantly improving the methanol yield. The methanol selectivity of the catalyst can be improved when the carbon content is in the range of 1 to 30 mol%. As the carbon content increases, the methanol selectivity of the catalyst presents a volcano-shaped curve, wherein the best effect is achieved when the carbon content is 5 mol%, and CO 2 The conversion rate reached 20.3% and the methanol selectivity reached 95.2%. At the same carbon content, compared with the copper-based catalyst directly doped with carbon materials, the carbon-modified copper-based catalyst prepared by in-situ carbonization using soluble compounds as carbon sources can simultaneously improve the carbon dioxide conversion rate and methanol selectivity.
[0058] from Figure 1 From the EDS-mapping diagram of the copper-based catalyst β-CZZ prepared in Example 1, it can be found that in the carbon-modified copper-zinc-zirconium catalyst prepared by in-situ carbonization using β-cyclodextrin as the carbon source, C is uniformly dispersed on the catalyst surface and is tightly combined with the active component copper species.
[0059] from Figure 2 From the contact angle measurement diagrams of the copper-based catalysts prepared in Example 1 and Comparative Example 1, it can be found that the copper-based catalyst β-CZZ prepared in Example 1 has a larger contact angle, indicating that carbon modification of the catalyst surface can improve the hydrophobicity of the catalyst surface to a certain extent.
[0060] In order to evaluate the stability of the prepared catalyst, the performance of Example 1, Example 6 and Comparative Example 1 before and after heat resistance was compared. The heat resistance condition was 350° C. for 8 h. The results are shown in Table 2.
[0061] Table 2 Evaluation results of heat resistance stability of each example
[0062]
[0063] Reaction conditions: T = 220 °C, P = 3.0 MPa, H 2 / CO 2 =3, WHSV = 6000mLg cat -1 h -1
[0064] Heat resistance condition: 350℃ for 8h
[0065] From the results listed in Table 2, it can be found that compared with Comparative Example 1, the catalyst of the present invention is more heat resistant to CO 2The conversion rate and methanol selectivity hardly decreased, indicating that the carbon-modified copper-based catalyst prepared by the preparation method of the present invention has good structural stability, the surface carbon plays a role in structural confinement of copper species, inhibits the aggregation and deactivation of Cu active components during the heat-resistant process, and the carbon modification enhances the hydrophobicity of the catalyst surface, making the H generated during the reaction 2 Timely desorption of O helps to maintain the stability of the copper species valence state, so the catalyst still maintains high CO after heat resistance. 2 conversion rate and methanol selectivity, showing high thermal stability.
Claims
1. A method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide, wherein the components of the copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide include Cu, ZnO, ZrO2 or Al2O3 and an additive C, wherein the Cu, ZnO, ZrO2 or Al2O3 in the catalyst are uniformly dispersed, the additive C is uniformly dispersed on the surface of the catalyst, and is tightly combined with the active component copper species to promote the dispersion of the copper species. At the same time, it plays a certain limiting role on the copper species and enhances the hydrophobicity of the catalyst surface, so that the valence state of the copper species remains stable; the components in the catalyst are expressed in molar percentages as follows: Cu is 20-70%, Zn is 10-60%, Zr or Al is 1-20%, and C is 1-30%; the catalyst uses a copper source, a zinc source and a zirconium source or an aluminum source as raw materials, sodium carbonate as a precipitant, and a soluble organic compound as a carbon source, and adopts coprecipitation-in-situ carbonization-reduction to obtain a carbon-modified copper-based catalyst, characterized in that The specific steps include: 1) According to the feed ratio, a copper source, a zinc source, a zirconium source or an aluminum source is dissolved in water to prepare a metal salt solution; sodium carbonate is dissolved in water to prepare a sodium carbonate solution, and a carbon source is added into the water and ultrasonically stirred to obtain a solution containing a carbon source; 2) co-precipitating the metal salt solution and the sodium carbonate solution into the solution containing the carbon source under stirring, aging under stirring, and filtering and washing the precipitate to obtain a catalyst precursor; 3) After drying the catalyst precursor obtained in step 2), calcining it in an inert atmosphere for in-situ carbonization, and then reducing it with H2 / N2 to obtain a copper-based catalyst for hydrogenation of carbon dioxide to methanol.
2. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that The carbon source is one or more of β-cyclodextrin, polyethylene glycol (PEG), ethylene glycol (EG), glucose or soluble starch.
3. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that The copper source is copper nitrate or copper acetate; the zinc source is zinc nitrate or zinc acetate; the zirconium source is zirconium nitrate or zirconyl nitrate; and the aluminum source is aluminum nitrate or pseudo-boehmite.
4. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that The molar ratio of the total molar amount of the copper source, zinc source, zirconium source or aluminum source to carbon is 1:0.01-0.
3.
5. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that The specific operation of step 2) is as follows: at 10-80 ° C, the metal salt solution and the sodium carbonate solution are titrated in parallel into the solution containing the carbon source in step 1) and stirred for co-precipitation, maintaining the pH = 7-10. After precipitation, the solution is stirred and aged at 40-100 ° C for 0.5-24 h. The precipitate is washed with deionized water until no sodium ions are detected to obtain a catalyst precursor.
6. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that The drying conditions of the catalyst precursor in step 3) are: drying at 60-160°C for 10-15 h; the calcination conditions are: calcining at 300-500°C for 3-6 h in a nitrogen or argon atmosphere.
7. A copper-based catalyst for preparing methanol by hydrogenating carbon dioxide obtained according to the preparation method of any one of claims 1 to 6.
Citation Information
Patent Citations
Methanol catalyst synthesized by carbon dioxide hydrogenation, preparation method and application thereof
CN105013492A
Catalyst for synthesizing methanol by carbon dioxide hydrogenation and preparation method thereof
CN111790392A